Peramalan Curah Hujan di Kota Bandung dengan Metode SARIMA (Seasonal Autoregressive Integrated Moving Average) - Muhammad Ilham Hakiqi; Arif Firmansyah; Restu Arisanti (Department of Statistics ITS, 2022)
The need for future rainfall information, modeling and forecasting is important. The forecasting method is a method used to predict future conditions based on past data. Rainfall data is time-series data in the form of seasonality, a pattern that repeats at fixed time intervals, so the authors use the Seasonal Autoregressive Integrated Moving Average (SARIMA) method, which is appropriate for data with seasonal characteristics. The author takes monthly rainfall data in Bandung city for the period January 2016 to December 2021 to forecast rainfall in Bandung city for next year. After calculations using the SARIMA method, the best model for forecasting rainfall in the city of Bandung is then obtained, namely the SARIMA model (0,0,0)(0,1,1)12.